2023
DOI: 10.1136/lupus-2022-000874
|View full text |Cite
|
Sign up to set email alerts
|

A better self-efficacy is predictive of better health-related quality of life (HRQoL) in patients with systemic lupus erythematosus: data from the Almenara Lupus Cohort

Abstract: ObjectiveTo determine the possible predictive value of self-efficacy on health-related quality of life (HRQoL) in patients with SLE.MethodsPatients with SLE from the Almenara Lupus Cohort were included. Self-efficacy was ascertained with the six domains from the Patient-Reported Outcomes Measurement Information System (PROMIS) self-efficacy for managing chronic conditions. For PROMIS domains, a score of 50 is the average for a clinical population (people with a chronic condition), a higher score indicates that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…The study also indicated that the QOL was relatively poor for SLE patients aged >45 years, as compared to those aged ≤44 years. Older patients have lower resistance, potentially leading to various underlying diseases 25 and complications. 26 Additionally, as the psychological burden on SLE patients increases, their worries and concerns intensify.…”
Section: Discussionmentioning
confidence: 99%
“…The study also indicated that the QOL was relatively poor for SLE patients aged >45 years, as compared to those aged ≤44 years. Older patients have lower resistance, potentially leading to various underlying diseases 25 and complications. 26 Additionally, as the psychological burden on SLE patients increases, their worries and concerns intensify.…”
Section: Discussionmentioning
confidence: 99%
“…Implementing patient education programs as a self-management strategy might represent potential avenues for impacting HRQoL ( 61 ). Self-management is described as a skill set that can be used to maintain quality of life, often including but not limited to medication and nutrition care, social support, and disease knowledge ( 62 ).…”
Section: Methodsmentioning
confidence: 99%